The Impact of Malignancy on Assisted Reproductive Outcomes for Cancer Survivors: A Retrospective Case–Control Study - Li, Yuehong; Cai, Xuefen; Dong, Binhua; Wang, Qi; Yang, Xiaohui; Yu, Aili; Wei, Huijuan; Ke, Zhanghong; Sun, Pengming; Zheng, Beihong; Sun, Yan (Frontiers in Oncology, 2022)
Background Related studies have shown that it is safe for cancer patients to undergo assisted reproduction. However, studies on whether a history of cancer affects long-term reproductive outcomes in women who undergo assisted reproductive technology (ART) are scarce. In this study, we evaluated the long-term reproductive outcomes of patients with malignant tumors undergoing ART treatment and explored the impact of malignancy history on ART outcomes. Methods This retrospective study analyzed the clinical outcomes of patients with malignant tumors undergoing their first in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles compared with those of age-matched healthy infertile women at Fujian Maternity and Child Health Hospital between January 2003 and October 2020. We evaluated ovarian stimulation outcome, the pregnancy rate, the live birth rate, the risk of adverse obstetric outcomes and birth outcomes. Results This study included 59 patients in the cancer group for data analysis who had a history of malignancy. By matching, a total of 118 healthy infertile women were included in the control group. No statistically significant association was found in terms of age, duration of infertility, BMI, or insemination type between the two groups of patients. Thyroid cancer(45.8%) and gynecologic malignancies (44.07%) were the major cancer types in this study. There were statistically significant differences in the antral follicle count (AFC) (12.00 ± 7.86 vs. 14.90 ± 8.71, P=0.033), length of ovarian stimulation (9.98 ± 2.68 vs. 11.42 ± 2.43, P=0.033) and endometrial thickness on the trigger day (10.16 ± 3.11 vs. 10.84 ± 2.17, P<0.001) between the two groups. The total gonadotropin dose, number of oocytes retrieved, fertilization rate, cleavage rate, high-quality embryo rate, blastocyst rate and first-time embryo-transfer (ET) implantation rate were nonsignificantly lower in the cancer group than in the control group (P>0.05). There were no significant differences in the clinical pregnancy rate per ET cycle (32% vs. 40.39%, P=0.156), live birth rate per ET cycle (27% vs. 35.96%, P=0.119), miscarriage rate per ET cycle (5% vs. 4.43%, P=0.779), or preterm delivery rate per ET cycle (11.11% vs. 17.80%, P=0.547) between the two groups. Additionally, regression analysis showed that a history of malignancy was not a risk factor for reproductive outcomes. Conclusions Overall, it is feasible for women with a history of cancer to conceive using ART is feasible and their long-term reproductive outcomes are similar to these of healthy infertile women. A history of cancer does not decrease the number of retrieved oocytes, increase the risk of adverse obstetric outcomes or affect birth outcomes.